Agility and Change-of-Direction Speed are Independent Skills: Implications for Training for Agility in Invasion Sports. Issue 1 (February 2015) - Young, Warren B.; Dawson, Brian; Henry, Greg J.
This review explores the differences between agility in invasion sports (defined as including reactive decision-making) and change-of-direction speed (CODS), and highlights the implications for training. Correlations between agility tests and CODS tests indicate that they represent independent skills. Agility tests discriminate higher- from lower-standard athletes better than CODS tests, indicating that the cognitive element of agility is important to performance. Training studies have shown that the development of strength qualities can transfer to gains in CODS, but this has never been shown for agility. There is some evidence that the importance of physical qualities is greater for CODS than for agility. It was concluded that the reactive element should be included in agility training, testing and research. While there appears to be no research evidence for the benefits of strength and power training, there is some support for the use of small-sided games for improving agility.